Asymmetric Decentralization in A Unitary State: The Legitimization of The Sultan’s Daughter as The Governor of the Special Region of Yogyakarta - Anom Wahyu Asmorojati; Suyadi Suyadi; King Faisal Sulaiman (Jurnal Hukum Novelty, 2022)
Introduction to The Problem: A unitary state, which democratically runs government, in general rejects a monarchist system. But, Indonesia as a unitary state which applies democracy accepts the Special Region of Yogyakarta has a monarchical system through the application of asymmetric decentralization.Purpose: The aim of this research is to find the pattern of relationships and authority between a democratic unitary state and a monarchist regional government, in particular the Special Region of Yogyakarta.Methodology: This research is normative legal research which analyzes Law No. 13 of 2012 Concerning the Particularity of Yogyakarta, Regulations and Royal Decrees, and Royal Pronouncements.Findings: The research findings show that Indonesia applies asymmetric decentralization to bind a constitutional relationship with the Special Region of Yogyakarta which applies a monarchist system. Indonesia and Yogyakarta’s asymmetric decentralization has a uniqueness over the asymmetric decentralization in federal states, that is by promulgating the Sultan as the governor.  Although this promulgation accords with Law No. 13 of 2012 and the Hadiningrat Yogakarta Keraton (Palace) Regulation; however, of late both an internal and external polemic has arisen.  This polemic has been triggered by Constitutional Decision No. 88/ PUU-XIV/2016 and Royal Decree and Pronouncement which permits a female Sultan, whereas in the Law of Particularity and Royal Decree confirms the Sultan must be male. This polemic has the potential to give rise to a power struggle within the royal family which has serious implications for the asymmetric democratic system and the constitutional monarchy which to date has been developed by Indonesia and the Special Region of Yogyakarta. For this reason, this research recommends revisions be made to the Royal Decree so that there is gender justice resulting in women being able to have the opportunity to become the sultan. A female sultan can become a new discourse in the legal field and the science of government because it has wide implications for gender, political, and cultural and religious discourses.Paper Type: Research ArticleKeywords: Assymetric decentralization; constitutional monarchy; female sultan; and special region of Yogyakarta